2014
DOI: 10.4314/ajtcam.v11i4.4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition profiling and antifungal activity of the essential oil and plant extracts of <i>Mesembryanthemum edule</i> (L.) bolus leaves

Abstract: Background: Essential oil from Mesembryanthemum edule leaves have been used by the Eastern Cape traditional healers for the treatment of respiratory tract infections, tuberculosis, dysentery, diabetic mellitus, laryngitis and vaginal infections. The investigation of bioactive compounds in the essential oil of this plant could help to verify the efficacy of the plant in the management or treatment of these illnesses. Materials and methods: Various concentrations of the hydro-distilled essential oil, ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…These reports come mainly from its native area (Matsiliza and Barker 2001;Van Wyk, de Wet, and Van Heerden 2008), but its use to treat hemorrhoids by local people have also been reported in Campania, southern Italy (Motti, Antignani, and Idolo 2009). Carpobrotus edulis has also been credited with anticancer (Ordway et al 2003), anti-bacterial (van der Watt and Pretorius 2001) and antifungal properties (Omoruyi, Afolayan, and Bradley 2014).…”
Section: Economic Importance and Human Usesmentioning
confidence: 99%
“…These reports come mainly from its native area (Matsiliza and Barker 2001;Van Wyk, de Wet, and Van Heerden 2008), but its use to treat hemorrhoids by local people have also been reported in Campania, southern Italy (Motti, Antignani, and Idolo 2009). Carpobrotus edulis has also been credited with anticancer (Ordway et al 2003), anti-bacterial (van der Watt and Pretorius 2001) and antifungal properties (Omoruyi, Afolayan, and Bradley 2014).…”
Section: Economic Importance and Human Usesmentioning
confidence: 99%
“…These oxygenated compounds have the ability to inhibit microbial causing infections [26]. Phytol administered to mice at increasing dose responds of 25, 50, 10, and 200 mg/kg showed pronounced anti-nociceptive effects in the nociception models used [27, 28].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, n-hexadecanoic acid represented the phytocomponent with the lowest concentration among the entire phytocomponents present in AqEUF of C. papaya. Tetradecanoic acid (myristic acid) has been detected in methanolic leaf extracts of J. rubens, C. mediterranea and P. capillacea [26], L. inermis [36] and hexane/acetone leaf extracts of M. edule [29]. Previous studies showed that tetradecanoic acid was the major antibacterial and antioxidant principles isolated from Myristica fragrans (nutmeg) [39,40] as well as antibacterial agent from P. capillacea [41].…”
Section: Resultsmentioning
confidence: 99%
“…Like AqEUF of C. papaya, octadecanoic acid is a major phytocomponent of hexane leaf extract of Mesembryanthemum edule used for the treatment of respiratory tract infections, tuberculosis, dysentery, diabetic mellitus, laryngitis and vaginal infections by Eastern Cape traditional healers [29]. Octadecanoic acid from Azadirachta indica (neem) extracts [30] and marine red seaweeds, namely, Jania rubens, Corallina mediterranea and P. capillacea exhibited antibacterial activity against Staphylococcus aureus, Escherichia coli and Salmonella spp [26].…”
Section: Discussionmentioning
confidence: 99%